Direct photochemical route to azoxybenzenes via nitroarene homocoupling. Issue 36 (8th September 2022) - Yaghoubian, Ali; Hodgson, Gregory K.; Adler, Marc J.; Impellizzeri, Stefania
Abstract : Ultraviolet illumination of nitrobenzenes at 365 nm produces their azoxy counterparts through a direct photochemical route. Abstract : We report on a direct photochemical method for the one-pot, catalyst- and additive-free synthesis of azoxybenzene and substituted azoxy derivatives from nitrobenzene building blocks. This reaction is conducted at room temperature and under air, and can be applied to substrates with a wide range of substituents. Yields of products derived from para - and meta -substituted nitrobenzenes are typically good, while sterically encumbered ortho -substituted substrates are not as fruitful. Photochemical Wallach rearrangement of generated azoxybenzenes to ortho -hydroxyazoxybenzenes was observed in some cases, most markedly in selected ortho -halogenated nitrobenzenes. Overall, this method provides an efficient, green pathway to highly value-added azoxybenzene products.